A microscopical and ultrastructural analysis of the embryonic epidermis of the pool frog, Pelophylax lessonae (Camerano, 1882) (Anura: Ranidae) - D. SEMERARO; D. MENTINO; R. ROSSI; G. SCILLITANI; M. V. GUGLIELMI; M. MASTRODONATO (The European Zoological Journal)
We analysed the embryonic epidermis of the pool frog, Pelophylax lessonae, by light and electron microscopy techniques, and characterized preliminarily its mucous secretions with conventional histochemistry (Toluidine Blue, Periodic Acid-Schiff, Alcian blue pH 2.5 and Alcian blue pH 1.0). At Gosner’s developmental stage 21, the epidermis consisted of a bilayered epithelium with five cell types. Basal cells (BCs) constituted the basal layer, presented a large nucleus and were sometimes observed in mitosis. Ciliated cells (CCs) had a ciliated apical membrane, with carboxylated glycans in the sub-apical portion. TEM analysis revealed small vesicles just below the surface, a central nucleus, and evident yolk plates. Goblet cells (GCs) and small secretory cells (SSCs) showed secreting vesicles and vacuoles, respectively. In the mucus secretion of GCs sialosulphomucins appeared, while in that of SSCs sulphation was not observed. Under TEM, GCs had irregular shaped nuclei and a less electron-dense cytoplasm with respect to SSCs. Ionocytes (INs) presented apical microvilli and a high electron-dense cytoplasm with vacuoles. SEM analysis revealed that GCs outnumbered the other cell types and that SSCs and INs were usually located together near to GCs. The relatively simple structure of the epidermis and its direct interfacing with the environment renders it a good model for the study of structure and development of mucociliary epithelia, as well as of its alterations in the presence of toxicants.